Pengaruh Pelatihan, Disiplin Kerja, dan Motivasi Intrinsik terhadap Kualitas Sumber Daya Manusia Studi pada Dinas Lingkungan Hidup dan Kehutanan Daerah Istimewa Yogyakarta - I. Soni Kurniawan; Epsilandri Septyarini; Lina Putri Angesti (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study was to determine the effect of training, work discipline, and intrinsic motivation on the quality of human resources of the Dinas Linkungan Hidup dan Kehutanan DIY employee. The population and samples used in this study were employees of the Dinas Lingkungan Hidup dan Kehutanan DIY. totaling 90 people and a sample of 60 people using purposive sampling method. The data collection method uses the distribution of questionnaires. Data analysis using validity and reliability tests and through two stages of testing, namely: classical assumption test and hypothesis testing (t test and F test). The results of this study indicate that training has no effect on the quality of human resources. There is a positive and significant influence on work discipline variables and intrinsic motivation on the quality of employee human resources and training, work discipline, and intrinsic motivation affect the quality of human in the Dinas Lingkungan Hidup dan Kehutanan DIY.